Plagiarisme Bisnis Kuliner Lintas Negara: Analisis Etika dan Hukum pada Kasus Bakery di Indonesia - Amelia Mara Jasmine; Halimah Zahrah; Bellia Aghata; Dewi Putri Angelina; Ditta Rahmawati (Indo Publishing, 2025)
Plagiarism in the culinary business is now a frequent issue, especially when it involves two countries such as Indonesia and Australia. This study discusses the alleged plagiarism of the business concept carried out by Circles Bakery against Publique Bakery, starting from the appearance of their cakes, logos, and interior designs. The purpose of this study is to review the case from the perspective of business ethics and applicable legal regulations, both nationally and internationally. The study uses a qualitative approach with a case study method. The focus of this study is Circles Bakery as the perpetrator and Publique Bakery as the party suspected of being copied. Data were obtained from various sources such as media articles, social media uploads, and other supporting information relevant to the case. Researchers chose these sources deliberately because they were considered most relevant to the topic. The collected data were analyzed by filtering important information, compiling it, and drawing conclusions from the existing findings. The results of the study indicate that although there have been no official lawsuits, the striking similarities in concept between the two businesses raise ethical questions and concerns about copyright protection. This study suggests that business actors, especially MSMEs, should value the originality of ideas more and understand the importance of running a business in an honest and ethical manner. In addition, stronger legal and educational support is needed to prevent similar cases in the future.